Inactivated Cells and Metabolites of Saccharomyces boulardii Alleviate Inflammation Damage in Caco-2 Monolayer Cells and Mice with Ulcerative Colitis - Yuxin Jin; Zehui Niu; Menglin Feng; Huilian Che; Zhihong Liang (Antioxidants, 2025)
Saccharomyces boulardii (S. boulardii) has attracted widespread attention due to its antimicrobial and anti-inflammatory properties. In this study, we prepared postbiotics from the heat-inactivated cells (HIC) and cell-free supernatant (CFS) of S. boulardii, with the important component L-arginine (Arg) from the metabolic products included as one of the experimental groups. The results showed that in LPS-stimulated Caco-2 cells, HIC, CFS, and Arg protect intestinal epithelial barrier integrity by inhibiting the expression of TNF-α, IL-1β, and IL-6 while enhancing the expression of occludin and ZO-1 proteins. In dextran sulfate sodium (DSS)-induced colitis mice, HIC, CFS, and Arg alleviate symptoms such as weight loss and colonic damage while suppressing the upregulation of pro-inflammatory factors and the downregulation of tight junction proteins. Moreover, these postbiotics help restore the gut microbiota composition and functionality in colitis mice, with potentially superior regulatory effects compared to sulfasalazine (SASP). Overall, HIC and CFS protect the intestinal barrier function and improve DSS-induced colitis, supporting the development of functional food supplements.